Program Peningkatan Kemampuan Digital Siswa Madrasah di Sumatera Barat - Volia, Loly (JURNAL ILMIAH GEMA PERENCANA, 2023)
This article describes that individual internet penetration in Indonesia has continued to increase during 2017–2021 to reach 62.10 percent in 2021. One indicator of information and communication technology development is the level of internet utilization. In general, this study aims to analyze opportunities for internet utilization in respondents with madrasah and Islamic boarding school education compared to public schools in West Sumatra. This can describe the successful implementation of ICT subjects for madrasah and Islamic boarding school students compared to general school students. Policy recommendations related to increasing digital skills in madrasah and Islamic boarding school students are based on the results of logistic regression statistical analysis on BPS September 2021 Susenas (National Socioeconomic Survey) data on 7,287 respondents in the West Sumatra region. The results of the descriptive analysis show that only 60 percent of respondents in West Sumatra use the internet. Statistically, all independent variables (region classification, age, gender, and education) have a significant effect on the opportunity to use the internet. Urban respondents have the opportunity to use the internet 2.69 times higher than respondents in rural areas. The opportunity for respondents who are teenagers (≤ 24 years old) to use the internet is 6.69 times higher than those who are adults. The opportunity for male respondents to use the internet is 1.27 times higher than that of women. Opportunities for respondents with educational background in madrasas and Islamic boarding schools to utilize the internet are 1.76 times higher than respondents with education in public schools.